1998
DOI: 10.1002/(sici)1097-4628(19980912)69:11<2097::aid-app1>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

A study of colored siloxane-based polyurethane ionomer

Abstract: ABSTRACT:The reaction of dye with toluene diisocyanate and dimethyldichlorosilane in the presence of other additives to form a colored siloxane-based polyurethane (PU) ionomer has been proven to occur by infrared spectra. In aqueous solution, the numberaverage particle size for the colored siloxane-based PU ionomer was found to increase with an increase in the NCO-to-OH ratio, dye concentration, and dimethyldichlorosilane concentration, as a result of increased free volume of the ionomer molecules. It is worth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The formed film tended to show the glass transition point of the soft segment, lower strength, and better elongation. Chao et al prepared a PU-based dye ionomer and found that the particle size became larger when the dye concentration was increased, and the formed film became stronger with decreased elongation [14][15][16]. Buruiana et al synthesized waterborne polyurethane with various covalently bonded chromophores [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The formed film tended to show the glass transition point of the soft segment, lower strength, and better elongation. Chao et al prepared a PU-based dye ionomer and found that the particle size became larger when the dye concentration was increased, and the formed film became stronger with decreased elongation [14][15][16]. Buruiana et al synthesized waterborne polyurethane with various covalently bonded chromophores [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the above flask a 0.1573 equivalent of toluene diisocyanate was subsequently added and reacted at 80–85°C for about 2 h to form a NCO‐terminated polyurethane (PU) prepolymer. A 0.034 equivalent of triethylamine was then reacted with this NCO‐terminated PU prepolymer in 80g acetone to form a quaternized NCO‐terminated PU prepolymer 2–8. This quaternized NCO‐terminated PU prepolymer further reacted with hydrolytes of dimethyldimethoxysilane (0.01 equivalent) or dimethyldiethoxysilane (0.01 equivalent), and 170 g water was then added to form the siloxane‐based PU ionomers with approximately 17.5% solids.…”
Section: Methodsmentioning
confidence: 99%
“…In general, two methods are used to improve their dyeing properties. One way is to change the PU structure and increase the number of dyeing sites, thus attracting more dyes and introducing the dye structure into the PU chain to produce a colourful PU polymer 5‐13 . However, polymer modification alters the mechanical properties of the PU polymer, leading to an undesirable result.…”
Section: Introductionmentioning
confidence: 99%